HUBUNGAN ANTARA MOTIVASI KERJA, TINGKAT PENDIDIKAN DAN PENGALAMAN PELATIHAN DENGAN KINERJA PEGAWAI DINAS PENDIDIKAN KOTA MALANG. - Martinus M. KROWIN (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2015)
The aim of this research is to know the correlation between the working motivation , the level of the education and the expirience of the training and the performance of he staff in the Education Service in Malang Regency. The problem formulations are : (1) How is the performance the staff of Education Service in Malang Regency ?,{2) How is the education level of the staff of Education Service in Malang Regency ? (3) How is the education level of the staff of Education Service in Malang Regency ? (4) How is the education level of the staff of Education Service in Malang Regency ? (5) How is the motivation  of the staff of Education Service in Malang Regency ?  (6) How is the education level of the staff of Education Service in Malang Regency ?, (7) How is the performance of the staff of Education Service in Malang Regency ?. To solve  the problems above this research is designed as fllowss (1).The discriptive problems will be solved in the discriptive report.(2).To solve the quantitative problems will be solved in statistical way.For the second problem the design is correlation one held in Malang.The sample is using  Krejcie Table by Proportionate Stratified Random Sampling .It is , therefore , the sample is 103 persons among 135 persons as population.                The results of the research by SPSS  are (1) The motivation of the staff of the Education Service in Malang is good.(2) The education level  of the staff of the Education Service in Malang is good. (3) The training exxperience of the staff of the Education Service in Malang is very law. (4) The performance  of the staff of the Education Service in Malang is good. (5) There is found it is a  positive correlation  between the motivation and the performance of the staff of the Education Service in Malang (6) There is a significant correlation  between the education level and the performance of the staff of the Education Service in Malang dan (7) (6) There is a significant correlation  between the training experience and the performance of the staff of the Education Service in Malang.Based on the results abaove , the researcher suggests as in the following among are  (1) The head of the education service in Malang always pays attention to the ability of the staff by as much as possible to send them to the training. (2) The head of the education service in Malang always pays attention to the ability of the staff by as much as possible to send them to continue their studies.(3) The head of the education service in Malang always pays attention to the ability of the staff by as much as possible to pay the finance of the training. (4) The head of the education service in Malang always pays attention to the ability of the staff by as much as possible to send them to the training. (5) The experrience of the staff training is only to give a small effect to the performancee  so it is good to evaluate the training activities.